ANALYSIS OF THE EFFECTIVENESS OF THE PERSONNEL ADMINISTRATION INFORMATION SYSTEM IN SUPPORTING EMPLOYEE PERFORMANCE AT THE MORO'O DISTRICT OFFICE OF WEST NIAS DISTRICT - Vivi Kristiani Gulo; Syah Abadi Mendrofa; Robin Markus Putra Waruwu; Dedi Irawan Zebua (Jurnal Ilmiah METADATA, 2026)
This research is entitled "Analysis of the Effectiveness of the Personnel Administration Information System in Supporting Employee Performance at the Moro'o Sub-district Office, West Nias Regency". The background of the research is based on the phenomenon of the implementation of the personnel administration information system that is not optimal, characterized by delays in data input, inconsistencies in employee information, and minimal utilization of system features. The purpose of this research is to analyze the effectiveness of the personnel administration information system in supporting employee performance, as well as to identify supporting and inhibiting factors for its implementation. This research uses a qualitative approach with data collection techniques through interviews, observations, and documentation. The results show that the personnel administration information system has provided benefits in increasing work efficiency, accelerating data access, increasing the timeliness of task completion, and encouraging employee discipline. However, the effectiveness of the system is not fully optimal due to limited facilities, lack of training, and the absence of regular evaluations. Thus, the personnel administration information system has a positive contribution to improving employee performance, although improvements are still needed in technical and human resource aspects.